2007
DOI: 10.1002/bies.20537
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chemotactic networks by ‘atypical’ receptors

Abstract: Directed cell migration is a fundamental component of numerous biological systems and is critical to the pathology of many diseases. Although the importance of secreted chemoattractant factors in providing navigational cues to migrating cells bearing specific chemoattractant receptors is now well-established, how the function of these factors is regulated is not so well understood and may be of key importance to the design of new therapeutics for numerous human diseases. While regulation of migration clearly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 73 publications
1
75
0
Order By: Relevance
“…Formerly known as CCR11 [33], CCXCKR is now regarded as being non-signalling and thus to be a member of the atypical family of chemokine 'receptors' [34,35]. In keeping with the lack of signalling, the DRY motif in human CCXCKR is altered to DRYVAVT.…”
Section: Ccxckrmentioning
confidence: 91%
See 1 more Smart Citation
“…Formerly known as CCR11 [33], CCXCKR is now regarded as being non-signalling and thus to be a member of the atypical family of chemokine 'receptors' [34,35]. In keeping with the lack of signalling, the DRY motif in human CCXCKR is altered to DRYVAVT.…”
Section: Ccxckrmentioning
confidence: 91%
“…In keeping with the lack of signalling, the DRY motif in human CCXCKR is altered to DRYVAVT. CCXCKR binds three homeostatic chemokines, CCL19, (Table 1), and appears to be capable of internalising these ligands and targeting them for intracellular degradation [36,37] in much the same way as is described below, in more detail, for D6 in the section In vitro studies of D6 function [34,35] (Fig. 1).…”
Section: Ccxckrmentioning
confidence: 94%
“…Whereas the binding of SDF1 to CXCR4 drives the migration (David et al, 2002), CXCR7 acts as an atypical receptor (Comerford et al, 2007) that may sequester SDF1 (Balabanian et al, 2005) in the trailing region of the primordium and thereby provide directionality to the migration . Alternatively or additionally, CXCR7 may contribute to migration independently of CXCR4 (Valentin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the internalization of chemokines from one side of the cell and appearing them from another cell surface. 30 However, further studies confirming the CCX-CKR is necessary to support this function. Studies conducted in 2013 showed a new role for this protein.…”
Section: Ccx-ckr (Ccrl1) Proteinsmentioning
confidence: 99%
“…Because of this, cells would not polarize or migrate. 30 Atypical chemokine receptors together with normal chemokine receptors usually are expressed in wide areas and are rarely found in the blood leukocytes. These receptors also bind with different chemokines; for instance, D6 protein binds to CC and CXC.…”
Section: Silent Chemokine Receptorsmentioning
confidence: 99%